“Questi giovani sono assurdi”. Rappresentazioni, miti e disuguaglianze nella cultura di massa dal dopoguerra agli anni Settanta - Molesini, Cecilia (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
This article examines representations of young people and youth in Italian mass culture from the postwar period to the 1970s through the weekly magazine «Oggi». Widely circulated and addressed to a broad, mainly conservative readership, «Oggi» offers a valuable lens on how young people were portrayed, perceived, and addressed by the adult world. By analysing articles, images, advertisements, and readers’ letters, this contribution reconstructs dominant myths, behavioural models, and social expectations surrounding youth. Despite major social transformations, the magazine reveals strong continuities in depicting young people as a distinct, often problematic and “dangerous” social group within bourgeois culture.